PENERAPAN AKUNTANSI DAN KESESUAIANNYA DENGAN SAK-EMKM PADA PERUSAHAAN MANUFAKTUR (STUDI KASUS PT XYZ KEDIRI) - Khusna, Masro'ul; Linawati, Linawati; Zaman, Badrus (Universitas Nusantara PGRI Kediri, 2022)
The rapid growth of MSMEs affects the strength of capital. MSMEs are growing rapidly making capital loans to banks/investor. However, not all MSMEs can get credit easily, due to unfulfilled requirements. Financial statements that do’nt meet the standards. PT XYZ does’nt yet know about SAK-EMKM-based financial reports that became active on January 1, 2018. This study is to find out: 1) PT XYZ SAK-EMKM implementation, 2) Factors causing MSMEs have not implemented SAK-EMKM to prepare financial reports. The descriptive qualitative method was employed in this investigation. Collecting data obtained through documentation and interviews of financial statements. The findings indicate that PT XYZ has not recorded financial statements in their entirety in line with SAK-EMKM. At PT XYZ, the elements that cause SAK-EMKM are not in place, internal factors are the HR and SAK are not understood. The absence of oversight from parties interested in MSMEs' financial disclosures is an external factor